2018
DOI: 10.1002/jid.3391
|View full text |Cite
|
Sign up to set email alerts
|

What Interactions between Financial Globalization and Instability?—Growth in Developing Countries

Abstract: This paper tests the effects of the impact of financial globalization on economic growth, examining its interaction with financial instability for a sample of 72 developing countries over the period 1972-2011, using dynamic panel estimator 'two-step Generalized Method of Moments' (two-step system GMM). The main results of the paper are the following: (i) financial instability and indebtedness-globalization decrease growth; (ii) financial globalization and investment-globalization increase growth; (iii) indebte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 58 publications
(93 reference statements)
1
7
0
Order By: Relevance
“…The results are reported in table 2 (see appendix) for the various specifications described in the previous section (with or without interactions). The validity of the GMM system estimator is conditioned upon the exogeneity of the instruments (Hansen test of over-identifying restrictions), as well as no autocorrelation of errors of order 2 (Arellano-Bond test AR2) (Gaies et al, 2019b). The tests confirm the validity of our benchmark models 1 and 5.…”
Section: Empirical Strategy: An Investment Behavior Equationsupporting
confidence: 61%
See 1 more Smart Citation
“…The results are reported in table 2 (see appendix) for the various specifications described in the previous section (with or without interactions). The validity of the GMM system estimator is conditioned upon the exogeneity of the instruments (Hansen test of over-identifying restrictions), as well as no autocorrelation of errors of order 2 (Arellano-Bond test AR2) (Gaies et al, 2019b). The tests confirm the validity of our benchmark models 1 and 5.…”
Section: Empirical Strategy: An Investment Behavior Equationsupporting
confidence: 61%
“…This classical estimator (difference GMM) for linear dynamic panel data may suffer from small sample bias and is not robust to heteroskedasticity. To consider this problem, following Gaies et al (2019b), we use instead the GMM system dynamic panel data estimator (Two-step system GMM) developed by Arellano and Bover (1995) and Blundell and Bond (1998), and we compute robust two-step standard errors by following the methodology proposed by Windmeijer (2005). The same model has been estimated by recent papers on capital constraints (within the ECM framework (e.g.…”
Section: Empirical Strategy: An Investment Behavior Equationmentioning
confidence: 99%
“…Even estimators based on exogenous instrumental variables, such as the two-and three-stage least squares (2SLS; 3SLS) estimators, may not account for endogeneity because of the weakness of exogenous instruments. 5 For these concerns, following recent empirical applications of dynamic growth models using panel data (e.g., [10,30,33,34], we use the panel GMM approach to estimate Eq. (11).…”
Section: Estimationsmentioning
confidence: 99%
“…We generate robust one-and two-step standard errors according to the Windmeijer[38] methodology, which is detailed by Roodman[32] and Windmeijer et al[39] using the Stata code: xtabond2 5. For more detailed explanations, see Roodman[32], Gaies et al[33] and Windmeijer et al[38].…”
mentioning
confidence: 99%
“…Apart from Hermes and Lensink (2008), who focus on emerging economies, only a small number of studies have found a direct global positive impact of external financing on economic growth in developing countries (Abraham & Schmukler, 2018;Gaies et al, 2019a;Kose et al, 2009).Worse still, when empirical models take into account the financial instability that could be induced by external capital flows, the positive spillover effect of external financing on the financial sector disappears. In addition, Batuo, Mlambo, and Asongu (2018), Gaies, Goutte, and Guesmi (2019b), and Loayza and Rancière (2006) show that although external financing can develop certain aspects of the financial sector, particularly financial deepening in developing countries, it contributes strongly to its destabilization, which can harm the financing of long-term growth and implies unsustainable economic development, especially if the financing is based on external debt. Even more so, Lee, Hsieh, and Dai (2012) find that the competition between the foreign bank, providing external funds, and the domestic bank could decrease the profitability of the latter.…”
Section: Empirical Evidencementioning
confidence: 99%